Behavioural diversity in chimpanzees and bonobos - Boesch, Christophe; Hohmann, Gottfried, 1951-; Marchant, Linda F. (Linda Frances), 1951- (Cambridge University Press, 2002)
Chimpanzees (Pan troglodytes) and bonobos (Pan paniscus), otherwise known as pygmy chimpanzees, are the only two species of the genus Pan. As they are our nearest relatives, there has been much research devoted to investigating the similarities and differences between them. This book offers an extensive review of the most recent observations to come from field studies on the diversity of Pan social behaviour, with contributions from many of the world's leading experts in this field. A wide range of social behaviours is discussed including tool use, hunting, reproductive strategies and conflict management as well as demographic variables and ecological constraints. In addition to interspecies behavioural diversity, this text describes exciting new research into variations between different populations of the same species. Researchers and students working in the fields of primatology, anthropology and zoology will find this a fascinating read.